A PD-L1/EGFR bispecific antibody combines immune checkpoint blockade and direct anti-cancer action for an enhanced anti-tumor response - Laura Rubio-Pérez; Rodrigo Lázaro-Gorines; Seandean L. Harwood; Marta Compte; Rocío Navarro; Antonio Tapia-Galisteo; Jaume Bonet; Belén Blanco; Simon Lykkemark; Ángel Ramírez-Fernández; Mariola Ferreras-Gutiérrez; Carmen Domínguez-Alonso; et al. (OncoImmunology)
Immune checkpoint blockade (ICB) with antibodies has shown durable clinical responses in a wide range of cancer types, but the overall response rate is still limited. Other effective therapeutic modalities to increase the ICB response rates are urgently needed. New bispecific antibody (bsAb) formats combining the ICB effect and a direct action on cancer cells could improve the efficacy of current immunotherapies. Here, we report the development of a PD-L1/EGFR symmetric bsAb by fusing a dual-targeting tandem trimmer body with the human IgG1 hinge and Fc regions. The bsAb was characterized in vitro and the antitumor efficacy was evaluated in humanized mice bearing xenografts of aggressive triple-negative breast cancer and lung cancer. The IgG-like hexavalent bsAb, designated IgTT-1E, was able to simultaneously bind both EGFR and PD-L1 antigens, inhibit EGF-mediated proliferation, effectively block PD-1/PD-L1 interaction, and induce strong antigen-specific antibody-dependent cellular cytotoxicity activity in vitro. Potent therapeutic efficacies of IgTT-1E in two different humanized mouse models were observed, where tumor growth control was associated with a significantly increased proportion of CD8+ T cells. These results support the development of IgTT-1E for the treatment of EGFR+ cancers.